Peran Opini Audit Wajar Tanpa Pengecualian Dan Fundamental Dalam Mempengaruhi Return Saham - Handayani, Revita Dwi (Gorontalo Accounting Journal, 2024)
The audit opinion is one of the factors that investors consider when buying or selling shares. This research was conducted to determine the role of audit opinions and fundamenta analysize in influencing return stock on the Indonesia Stock Exchange. This study was a quantitative research approach that used secondary data. The population of this research consisted of 790 companies listed on the Indonesia Stock Exchange, based on purposive sampling technique a total of 430 were selected as the research sample during the study period from 2018 to 2021. This research utilized panel regression analysis and used Eviews 9 application. The research findings indicate that the audit opinions with unqualified opinion and return on asset in this study played a role in the company's stock returns and current ratio has no role in the company’s stock returns.